Nevermoor: The Trials of Morrigan Crow - Townsend, Jessica (UK Hodder & Stoughton, 2018)
Morrigan Crow is cursed, destined to die on her eleventh birthday. But, as the clock strikes midnight, she's whisked away by a remarkable man called Jupiter North and taken to the secret city of Nevermoor. There she's invited to join the Wundrous Society. Mystery, magic and protection are hers - if only she can pass four impossible trials, using an exceptional talent. Which she doesn't have...